COMMUNITY EMPOWERMENT IN LOCAL GOVERNMENT DECISION MAKING: A SYSTEMATIC REVIEW OF MODELS AND IMPLEMENTATION - Arum Apriyani; Hendayana; Selvi Diana Meilinda; Azharisman Rozie (ipdn, 2025)
This study presents a systematic review of community empowerment in local government decision-making, with a focus on prevailing models and patterns of implementation. A structured search of Scopus and Google Scholar identified more than 800 initial records. Following PRISMA procedures, 62 studies met the inclusion criteria and were analysed in depth. Data were extracted and coded by geographical context, type of participatory model, degree of citizen influence, process quality, level of institutionalization, political commitment, and reported policy outcomes. The synthesis identifies several main configurations of community empowerment and shows that the expansion of participatory mechanisms at the local level has not been accompanied by a consistent deepening of citizen power; most initiatives remain at low to moderate levels of influence. Higher empowerment scores tend to be associated with better-designed participatory processes and stronger policy outcomes, but these relationships are conditional rather than deterministic. Institutionalization and political commitment emerge as enabling conditions, yet they are not sufficient on their own to ensure substantive power sharing. Overall, the findings indicate that community empowerment in local government is highly dependent on institutional design, political context, and deliberate strategies for inclusion, accountability, and redistribution, rather than on the mere adoption of participatory instruments.